63.0k views
2 votes
Solve

9(a + 2b) + c

a = 3
b = 2
c = 1

2 Answers

3 votes

Answer:

64

Explanation:

Substitute in the numeric values for the variables, and now you have

9(3+2(2)) +1. Simplify, and now you have 9(3+4) +1. Use pemdas to get 7 for the value in the parentheses, and then multiply 9 and 7 to get 63. Add 1 and 63 and now you have 64.

User Elmer Dantas
by
6.3k points
1 vote

Answer:

64

Explanation:

Step 1: Define

9(a + 2b) + c

a = 3

b = 2

c = 1

Step 2: Substitute and Evaluate

9(3 + 2(2)) + 1

9(3 + 4) + 1

9(7) + 1

63 + 1

64

User Rajind Ruparathna
by
6.3k points